Pathways to Middle-Class Jobs in Indonesia - Wihardja, Maria Monica; Cunningham, Wendy (World Bank, Washington, DC, 2021)
‘Our dream, our ambition is that by 2045, after one century of Indonesian independence, Indonesia should, Insya Allah (God willing), have escaped the middle-income trap,' President Joko Widodo declared in the opening lines of his inaugural address in October 2019. Indonesia is on its way, with single digit poverty rates and economic growth averaging 5 percent annually between 1990 and 2018. However, nearly half (47 percent) of Indonesians are stuck just below the middle-class threshold and belong to an ‘aspiring middle class.’ They are neither poor, nor highly vulnerable to becoming poor, but have not reached a level or stability of consumption associated with middle-class status. Indonesia’s jobs situation may be preventing the country from making rapid progress toward realizing its dream. Jobs have contributed to both growth and poverty reduction. Indonesia created an average of 2 million new jobs each year in the past decade. These take many forms, such as 40-hours-a-week Jakarta office jobs, food stalls run by families, online motorcycle taxi drivers, and subsistence farmers in Papua. In 2018, there were approximately 124 million working youth and adults in Indonesia, the employment rate had reached a two-decade record high, with 67.2 percent of youth and adults in the labor force, and the unemployment rate was at a two-decade low of 5.3 percent. This report posits that Indonesia is currently a story of growth in low-productivity jobs. Jobs are being created, and they fuel the economy, but productivity growth is insufficient to unlock the backlog of people aspiring, but unable, to move up to the middle class. This report explores the factors holding back productivity growth and thus the creation of middle-class jobs, and offers policy levers that could unlock the barriers. This Overview presents a cross-sectoral narrative about the current jobs situation and the policy framework that is needed to spur the creation of middle-class jobs toward a middle-class Indonesia. It draws from sector-specific empirical analysis of the macroeconomy, and of firms and workers; the empirical analysis is presented in a companion technical report. The Overview is intended to give a broad picture of the challenge of creating middle-class jobs, identify potential policy priorities, and map out initial actions to move a complex agenda. The preparation of the report overlapped with the COVID-19 crisis. While it refers to the economic crisis caused by the pandemic, it primarily looks toward a post-COVID-19 period of rebuilding better.